Effects of Semaglutide versus Bariatric Surgery on Noninvasive Markers of Hepatic Steatosis and Fibrosis in Obesity with MASLD - Paula Lünswilken; Katarzyna Worobiec; Lara S Braun; Julia Altrogge; Andrea Schenk; Lina Jegodzinski; Britta Wilms; Jens U Marquardt; Svenja Meyhöfer (The Journal of Clinical Endocrinology & Metabolism, 2026)
Abstract Aims Obesity is a key driver of metabolic dysfunction-associated steatotic liver disease (MASLD). Beyond lifestyle modification, pharmacological and surgical therapies were recently established. This study compared the effects of lifestyle therapy, lifestyle plus semaglutide, and bariatric surgery on non-invasive markers of hepatic steatosis and fibrosis. Materials and Methods In this single-center, prospective, observational cohort study, ninety-two adults with obesity were analyzed over 72 weeks. Patients received (1) lifestyle-based multimodal therapy ([LIFESTYLE], n = 30), (2) lifestyle plus semaglutide therapy ([SEMA], n = 30, semaglutide 1.0 ± 0.4 mg/week), or (3) lifestyle plus laparoscopic sleeve gastrectomy (LSG) ([SURGERY], n = 32). Controlled attenuation parameter (CAP) and liver stiffness measurement (LSM) were assessed using FibroScan®; Fibrosis-4 (FIB-4) and FibroScan-AST (FAST)-scores were calculated. Results At baseline, all patients showed hepatic steatosis. Over 72 weeks, CAP decreased significantly (p < 0.001) with reduction of –17.9 ± 14.0 [LIFESTYLE], –46.0 ± 14.0 [SEMA], and –83.7 ± 10.0 dB/m [SURGERY], respectively (overall p = 0.002). Baseline LSM differed between groups and declined by –0.8 ± 1.0, –2.8± 0.8, and –4.9 ± 1.1 kPa, respectively (overall p < 0.001), without significant differences between SEMA and SURGERY in relative reduction (p = 0.428). FAST scores decreased significantly over time across all groups (p < 0.001). FIB-4 increased modestly after SURGERY (+0.29; p < 0.001), while remaining stable in SEMA and LIFESTYLE (both p > 0.3). Weight loss amounted to –4.2 ± 1.8, –10.7 ± 1.5 and –31.6 ± 1.5%. LSM improvement was weight-dependent in SURGERY (p = 0.027), while LSM improvement in SEMA occurred independently of weight change (p = 0.508). Conclusions Semaglutide and LSG both improved non-invasive markers for hepatic steatosis and fibrosis, whereas lifestyle intervention alone showed limited benefit. Despite differing degrees of weight loss, adjusted liver stiffness did not differ significantly between semaglutide and surgery, a hypothesis-generating finding that warrants further investigation into weight-independent mechanisms.